Business continuity and disaster recovery for infosec managers - Rittinghouse, John W.; Ransome, James F. (Amsterdam ; Boston : Elsevier Digital Press, 2005)
Every year, nearly one in five businesses suffers a major disruption to its data or voice networks or communications systems. Since 9/11 it has become increasingly important for companies to implement a plan for disaster recovery. This comprehensive book addresses the operational and day-to-day security management requirements of business stability and disaster recovery planning specifically tailored for the needs and requirements of an Information Security Officer. This book has been written by battle tested security consultants who have based all the material, processes and problem- solving on real-world planning and recovery events in enterprise environments world wide. John has over 25 years experience in the IT and security sector. He is an often sought management consultant for large enterprise and is currently a member of the Federal Communication Commission's Homeland Security Network Reliability and Interoperability Council Focus Group on Cybersecurity, working in the Voice over Internet Protocol workgroup. James has over 30 years experience in security operations and technology assessment as a corporate security executive and positions within the intelligence, DoD, and federal law enforcement communities. He has a Ph. D. in information systems specializing in information security and is a member of Upsilon Pi Epsilon (UPE), the International Honor Society for the Computing and Information Disciplines. He is currently an Independent Consultant. Provides critical strategies for maintaining basic business functions when and if systems are shut down Establishes up to date methods and techniques for maintaining second site back up and recovery Gives managers viable and efficient processes that meet new government rules for saving and protecting data in the event of disasters.
Contingency and continuity planning -- Assessing risk -- Mitigation strategies -- Preparing for a possible emergency -- Disaster recovery phase -- Business recovery phase -- Testing, auditing, and training -- Maintaining a business continuity plan.
Includes bibliographical references (p. 275-281) and index.
Keywords: Business -- Data processing -- Security measures; Crisis management; Computer networks -- Security measures; Information resources management; Electronic books